2019
DOI: 10.1007/s13197-019-03823-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium benzoate application on quality and enzymatic changes of pear fruits during low temperature

Abstract: Effect of postharvest applications of sodium benzoate on physico-chemical properties and enzymatic activities of pear fruit cv. Patharnakh during cold storage were examined. Uniform and healthy fruits of pear cv. Patharnakh were treated with sodium benzoate (0.0, 1.0, 2.0 and 3.0%) and thereafter stored at low temperature conditions (0-1 °C and 90-95% RH) for 70 days. Evaluation of physico-chemical parameters and enzymatic activities were made at 0, 20, 40, 60 and 70 days of storage. Sodium benzoate treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Demes et al (2021) and Choudhary and Dhruve (2014) also supported the findings of this experiment on specific weight loss in tomato crops. Kaur et al (2019) in their experiment found that the effect of sodium benzoate on postharvest conditions helps to reduce the weight loss percentage. Similarly, Venkatram et al (2015) reported that the application of sodium benzoate on apples during storage also helped to reduce the weight loss percentage.…”
Section: Effect On Weight Loss Percent Of Tomatomentioning
confidence: 99%
“…Demes et al (2021) and Choudhary and Dhruve (2014) also supported the findings of this experiment on specific weight loss in tomato crops. Kaur et al (2019) in their experiment found that the effect of sodium benzoate on postharvest conditions helps to reduce the weight loss percentage. Similarly, Venkatram et al (2015) reported that the application of sodium benzoate on apples during storage also helped to reduce the weight loss percentage.…”
Section: Effect On Weight Loss Percent Of Tomatomentioning
confidence: 99%
“…The titratable acidity recorded the lowest decrease in SA treated strawberries as compared with the controls while dipping in 2% citric acid led to a sharper decline in it. A lower decrease in the titratable acidity may be attributed to a reduced respiratory rate as the decline of the titratable acidity in fruits has been attributed to the use of organic acids as respiratory substrates (Kaur et al 2019).…”
Section: Titratable Aciditymentioning
confidence: 99%
“…The control samples had significantly lower TA value than the treated samples during the last three weeks of storage. The initial increase of the titratable acidity could be attributed to the weight loss of the fruits while the decrease of TA in the later storage time is due to the consumption of organic acids in respiratory processes (Kaur et al, 2019).…”
Section: Titratable Aciditymentioning
confidence: 99%